2014
DOI: 10.1039/c4cp03240c
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray absorption spectroscopy of LiBF4 in propylene carbonate: a model lithium ion battery electrolyte

Abstract: Since their introduction into the commercial marketplace in 1991, lithium ion batteries have become increasingly ubiquitous in portable technology. Nevertheless, improvements to existing battery technology are necessary to expand their utility for larger-scale applications, such as electric vehicles. Advances may be realized from improvements to the liquid electrolyte; however, current understanding of the liquid structure and properties remains incomplete. X-ray absorption spectroscopy of solutions of LiBF4 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 52 publications
(80 reference statements)
14
50
1
Order By: Relevance
“…Although several experimental and theoretical works have focused on systems formed by pure EC, PC and DMC with the Li + ion [24][25][26][27][28][29][30][31] , solvation structure and dynamics of the cation in these solvents is still a subject of debate. More in details, Density Functional Theory (DFT) studies have shown that a (four-coordinated) tetrahedral geometry Li + (EC)4, is the dominant species [32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…Although several experimental and theoretical works have focused on systems formed by pure EC, PC and DMC with the Li + ion [24][25][26][27][28][29][30][31] , solvation structure and dynamics of the cation in these solvents is still a subject of debate. More in details, Density Functional Theory (DFT) studies have shown that a (four-coordinated) tetrahedral geometry Li + (EC)4, is the dominant species [32][33][34] .…”
Section: Introductionmentioning
confidence: 99%
“…We have recently used this combination of experimental and theoretical methodologies to study cation-cation pairing in aqueous solutions of guanidinium hydrochloride, 18 the hydrolysis of carbon dioxide in the carbon cycle, 19,20 and the solvation of Li + by propylene carbonate. 21 Here, we apply these techniques to the comparative study of ion solvation and pairing in aqueous solutions of NaNO 3 and NaNO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore ideal for probing liquid structure. Since introducing the use of liquid microjet technology in XAS of liquids in 2001, 45 we have employed this methodology to study a wide variety of phenomena in liquid systems, including ion solvation and pairing in water, 46,47 the solvation of lithium in propylene carbonate, 48 the hydrolysis of carbon dioxide, 49 and the structure of hydrated carbonic acid.…”
Section: -17mentioning
confidence: 99%